Pengaruh Penyuluhan Kesehatan terhadap Pengetahuan dan Sikap Tentang Diet Sehat pada Penderita Diabetes Melitus Tipe II RS Boloni Tahun 2025 - Suzan Fhitriana; Nora agustina; Sahala Sahala (Lembaga Pengembangan Kinerja Dosen, 2026)
Diabetes Mellitus Type 2 (DMT2) is 90% cases of all DM in the world, in Indonesia it reaches more than 16 million people and in Hospital Boloni Medan City in April 2025 as many as 54 people. This study aims to determine the effect of health education on knowledge and attitudes about a healthy diet in patients with type II diabetes mellitus at the Hospital Boloni Medan City in 2025. This research is a Quasy Experimental research with One Group Pretest Posttest design. The study was conducted at the Tomuan Health Center from October 2025 to March 2026. The sample of this study was 55 people with Diabetes Mellitus Type II. The analysis uses the t-paired sample test, which compares the data before and after being given counseling, and the mean difference between pre-test and post-test is obtained. The level of significance is 95% (α = 0,05). The results showed that there were 47 people who experienced an increase in knowledge after treatment, the mean rank was 25,91 and there was an increase in the average value of attitudes before treatment from 19,73 to 30,20 after treatment. The results of the statistical test of the knowledge variable obtained a p value of 0,000 < 0,05 and the attitude variable p value of 0.007 < 0,05. The conclusion of this study is that there is an effect of health education on knowledge and attitudes about a healthy diet in patients with Type II Diabetes Mellitus at the Hospital Boloni Medan City. It is hoped that DM patients will regularly follow health education to increase their knowledge about a healthy diet in patients with Type II Diabetes Mellitus.